A review of the effectiveness of virtual bronchoscopy in biopsy of lung tumors. Evolution of lung tumor diagnosis - Ziarnik, Kacper; Hofman, Michał; Krasowski, Michał (Journal of Education, Health and Sport, 2025)
Lung cancer remains the leading cause of cancer-related mortality, emphasizing the need for advanced diagnostic methods. This study reviews modern bronchoscopy navigational techniques, focusing on Virtual Bronchoscopic Navigation (VBN) and Electromagnetic Navigation Bronchoscopy (ENB), assessing their efficacy and safety in biopsying pulmonary lesions. Based on literature from 2000 to 2023, VBN demonstrated superior diagnostic accuracy for smaller nodules, with success rates of 93% vs 89% for ENB, while both methods exhibited low complication rates. Despite higher upfront costs, these technologies may offer long-term savings due to improved outcomes. Further research is warranted to optimize lung cancer diagnostics and enhance patient care. Aim of the study This study aims to evaluate the effectiveness and safety of VBN and ENB in diagnosing lung nodules. By comparing diagnostic success rates, complication rates, procedure durations, and cost-effectiveness, we seek to identify the safer and more efficient technique for biopsying neoplastic lesions, ultimately improving patient outcomes. Materials and methods We searched the following databases: PubMed, Web of Science, clinical trial registry platforms, using key terms such as virtual bronchoscopy navigation, navigation system-guided biopsy, bronchoscopic lung biopsy. The results were limited to papers published between 2000 - 2023. Conclusion Navigational bronchoscopy techniques like VBN and ENB are safe and effective, with minimal adverse events and no hospitalization needed. They reduce procedure times and patient burden, offering long-term cost-effectiveness despite higher initial costs. Further research is necessary to enhance these technologies for better lung cancer diagnostics. Key words: lung biopsy, bronchoscopy navigation, lung cancer, bronchoscopic